POJĘCIE PRAWA PODMIOTOWEGO WE WSPÓŁCZESNEJ LIBERALNEJ FILOZOFII PRAWA - Błachut, Michał (Wydział Prawa i Administracji UAM, 2002)
The article presents three viewpoints on the notion of right, all three deriving from different research perspectives. An attempt is made at finding connection between the concepts of W. N. Hohfeld, H. L. A. Hart, and R. Dworkin, making an assumption that the notion of right has an ethical dimension and its analysis cannot be free from axiological complications.
NOTION OF RIGHT IN CONTEMPORARY LIBERAL PHILOSOPHY OF LAW